Strategic Approach for Frustrating Charge Recombination of Perovskite Solar Cells in Low-Intensity Indoor Light: Insertion of Polar Small Molecules at the Interface of the Electron Transport Layer - Shin, So Jeong; Alosaimi, Ghaida; Choi, Min Jun; Ann, Myung Hyun; Jeon, Gyeong G.; Seidel, Jan; Kim, Jincheol; Yun, Jae Sung; Kim, Jong H. (ACS Applied Energy Materials, 2022)
In this study, we propose a strategic interface engineering method for optimizing the power density and power conversion efficiency (PCE) of perovskite solar cells (PVSCs) under low-intensity indoor light conditions. The insertion of a polar bathocuproine (BCP) layer at the electron transport interface significantly improved the photovoltaic properties, in particular, the fill factor and open circuit voltage, in a low-intensity light environment. Based on the systemic characterizations of surface trap states and carrier dynamics using Kelvin probe force microscopy, we revealed that BCP facilitated efficient charge carrier separation and electron extraction under low-intensity light illumination due to surface passivation and dipole-induced suppressed charge recombination. The beneficial role of BCP enabled excellent indoor PCEs of 27.04 and 35.45% under low-intensity light-emitting diode and halogen lights, respectively. Modification of the electron transport layer interface using polar molecules is a simple but highly effective method for optimizing the indoor performance of PVSCs.
Keywords: Bathocuproine; Charge recombinations; Electron transport layers; Indoor light; Low-intensity; Organic electron transport layer; Organics; Small molecules; Strategic approaches; Trap; defects; indoor light; organic electron transport layer; perovskite solar cells; trap